Randomized trial of laryngeal organ preservation evaluating two cycles of induction chemotherapy with platinum, docetaxel, and a novel Bcl‐xL inhibitor. Issue 7 (13th April 2022) - Swiecicki, Paul L.; Bellile, Emily; Casper, Keith; Chinn, Steven Bennett; Dragovic, Aleksandar F.; Jolly, Shruti; Kupfer, Robbi; Malloy, Kelly M.; Mierzwa, Michelle Lynn; Shuman, Andrew G.; Spector, Matthew E.; Srinivasan, Ashok; et al.
Abstract: Background: Single cycle induction chemotherapy (IC) with platinum and 5‐flurouracil (PF) and treatment based on clinical response predicts organ preservation in laryngeal cancer. Other agents offer intriguing alternatives with potentially increased ease of administration, reduced risk for severe toxicities, and increased platinum sensitivity. Methods: We report the results of a phase II bioselection trial in advanced resectable laryngeal cancer utilizing an IC regimen of two cycles of platinum plus docetaxel (TP) with a Bcl‐2 inhibitor. The primary endpoint was organ preservation rate at 12 weeks post chemoradiation. Results: Fifty‐four patients were enrolled. Response to IC was 72%. The organ preservation rate was 59% with a laryngectomy free survival of 46%. Induction related grade ≥3 toxicities were observed in 56% of patients with two grade 5 events. Conclusions: Two cycles of TP IC plus a Bcl‐2 inhibitor did not improve laryngeal preservation compared to a single cycle of PF.